Karakteristik Fisikokimia dan Sensoris Selai Pisang Tongka Langit (Musa troglodytarum) dengan Variasi Konsentrasi Pektin - Tuhumury, Helen Cynthia Dewi; Moniharapon, Erynola; Rahanra, Helta Chrisna; Sahetapy, Lorina (Jurnal Teknologi Hasil Pertanian, 2023)
The high content and benefits of beta carotene banana tongka langit make it important to be used as an ingredient in processed food products. One of the efforts to utilize sky tongka bananas is to make jam that can extend the shelf life and diversification of processed sky tongka bananas. This study aimed to determine the right concentration of pectin in producing sky tongka banana jam with the best physicochemical and sensory properties. The results showed that tongka langit banana jam made without the addition of pectin (0%) was the jam with the best physiochemical and sensory characteristics. Sky tongka banana jam has a moisture content of 52.90%; vitamin C 46.05 mg/100g; fiber 0.30%; total sugar 35.10%; total acid 3.55%; and total dissolved solids 32.15°Brix. Sky tongka banana jam without the addition of pectin (0%) has the highest percentage of favorability in almost all sensory categories, including taste, color, texture, and overall. This product has the characteristics of sky tongka banana taste, slightly aromatic sky tongka banana, yellow color, soft texture, and rather easy spreading.